The relationships between reading attitude, metacognitive awareness of reading strategies and reading motivation of L2 learners: A mediational analysis - Mahmoodi Shahrebabaki, Masoud; Oslund, Eric (Journal of Interdisciplinary Studies in Education, 2024)
The present study aimed to explore the relationship between reading attitude, motivation, and the metacognitive awareness of reading strategies (MARS) of adult EFL learners. Ninety-seven Iranian intermediate EFL learners participated in the study after a multi-stage sampling. The initial analysis suggested high correlations between the variables of attitude, motivation, and the metacognitive awareness of reading strategies. A mediation analysis using structural equation modeling was conducted to examine the intervening effect of MARS on the effect of attitude on motivation. The proposed model confirmed the mediational hypothesis with a good fit. The findings bear notable implications which are discussed in light of the study outcomes.